Dry air cyclic oxidation of mixed Y/Yb disilicate environmental barrier coatings and bare silica formers. Issue 7 (July 2022) - Stack, P.; Kane, K.; Sweet, M.; Parker, C.; Lance, M.; Ridley, M.; Pint, B.
Abstract: Mixed Y and Yb disilicate coatings (Y/Yb)DS have been proposed as dual function thermal and environmental barrier coatings (EBCs) for protecting SiC-based ceramic matrix composites in gas-turbine environments. As an initial step, the 1350 °C dry air cyclic oxidation of atmospheric plasma sprayed (Y1.2 /Yb0.8 )DS and ytterbium disilicate/ytterbium monosilicate (YbDS/YbMS) EBCs deposited onto Si bond coatings was compared. As a baseline for evaluating EBC oxidant permeability, the dry air cyclic oxidation scale growth rates for bare silica formers (SiC, Si) were also measured and were consistently higher than rates previously measured after isothermal oxidation. Regarding Si bond coat oxidation rates underlying (Y/Yb)DS and YbDS/YbMS EBCs, the thinner silica scale formed under the thinner and denser (Y/Yb)DS coatings suggested a lower oxidant permeability than YbDS/YbMS. After 500 1-h cycles, the (Y/Yb)DS coating was comprised of only the β-polymorph disilicate and minor amounts of the X-2 phase monosilicate phase. Negligible differences in oxidation kinetics for (Y/Yb)DS coatings over the 90 – 240 µm thickness range were observed.